Enhancing Electric Motor Control of Electric Motor Installation in Indonesian Vocational Schools Using PLC and VSD Technology with HMI - Made Suginardha, I; Ima Ismara, Ketut; Supriadi, Muhammad; Hariyanto, Didik; Meunmany, Santiphap (DPTE FT UNY, 2025)
Vocational education plays a crucial role in producing skilled labor that is prepared to meet industry demands. This research aims to develop a learning medium in the form of an Automated Sorting Conveyor System based on PLC, VSD, and HMI technology to enhance the competencies of vocational high school students in the subject of Electric Motor Installation. This study employs a Research and Development approach with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Feasibility testing was conducted by subject matter experts and media experts, while effectiveness testing was performed through pre-tests and post-tests with 33 eleventh-grade students at State Vocational High School 1 South Kuta. The validation results indicate that the media was rated highly feasible by experts (media: 84.17%, material: 95.17%). The use of Automated Sorting Conveyor System has proven effective in improving student learning outcomes, with an average gain score of 0.333 for theoretical aspects and 0.335 for practical aspects. This study recommends the use of Automated Sorting Conveyor System media in the practical learning of electric motor control in vocational schools, as well as training for teachers to optimize its use.